Nekateri vidiki gospodarskega prava EU po Beli knjigi o prihodnosti Evrope in v luči brexita - Grilc, Peter (Podjetje in delo, 2017)
The article examines the consequences of an EU Member withdrawing state from the integration, namely Brexit. It discusses general influences on the creation and enforcement of community law and models of economic integration, and specifically analyses individual areas of law, focusing on economic issues. These areas are civil law, the functioning of financial markets, corporate law and commercial law in the broad sense, insolvency, intellectual property, criminal law, competition law, recognition and enforcement of decisions, free movement of goods and free movement of persons.
Keywords: Bela knjiga o prihodnosti Evrope; brexit; civil law; civilno pravo; commercial law; common market; competition law; Court of Justice; criminal law; directives; direktive; European Commission; Evropska komisija; financial markets; finančni trgi; free movement of goods; free movement of persons; gospodarsko pravo; insolvenca; integration models; intelektualna lastnina; kazensko pravo; konkurenčno pravo; modeli integracije; priznanje in izvršitev odločb; prost pretok blaga; prost pretok oseb; recognition and enforcement of decisions; secondary legislation; sekundarna zakonodaja; skupni trg; Sodišče EU; White Paper on the future of Europe